Bilingualism and morphological awareness: a study with children from general education and Spanish-English dual language programs. Issue 2 (7th February 2017) - Kuo, Li-Jen; Ramirez, Gloria; de Marin, Sharon; Kim, Tae-Jin; Unal-Gezer, Melike
Abstract : Existing research on the impact of bilingualism on metalinguistic development has concentrated on the development of phonological awareness. The present study extended the scope of existing research by focusing on morphological awareness, an aspect of metalinguistic awareness that becomes increasingly important beyond the initial phase of literacy development. Participants included three groups of fourth-grader children from the same school with comparable SES and non-verbal IQ: (a) monolingual English-speaking children from a general education programme, (b) Spanish-speaking children from a Spanish–English dual-language programme and (c) English-speaking children from the same Spanish–English dual-language programme. Researcher-developed measures of vocabulary and morphological awareness were administered. Results suggested that bilingual education can have a positive impact on the development of morphological awareness through cross-language transfer as well as increased sensitivity to structural language features. The findings contribute to a growing body of research on how bilingual experience may shape children's metalinguistic development.